EXPLORING TEACHERS BELIEFS ON TEACHING METHODOLOGY IN THE 2013 CURRICULUM AND THE APPLICATION IN LANGUAGE TEACHING: A CASE STUDY AT MTS PPMI ASSALAAM SUKOHARJO - Ariffin, Zainal (Jurnal Penelitian Humaniora, 2017)
This article is a case study on exploring teachers beliefs on teaching methodology in the 2013 curriculum and their application in language teaching. The type of the research is a case study. It is an in depth study of a particular situation. The object of the research is beliefs on teaching methodology in The 2013 Curriculum and their Applications in Language Teaching at MTs PPMI Assalaam Sukoharjo. The subjects of the research were English teachers of MTs PPMI Assalaam Sukoharjo. There were two males and two females teachers. There are three kinds of data sources, namely field note, interview, and document which were taken from informants, documentation, and events. The writer applied four techniques of collecting data, namely open ended questionnaire, observation, in-depth interview, and documentation. The data validity used triangulation method to eliminate bias. It used Miles and Hubermans model in analyzing the data. This study, there were found the EFL teachers beliefs on teaching methodology in the 2013 curriculum and their application in the language teaching, namely learning objectives, syllabus, classroom management, teachers role, students role, instructional material and assessment. Besides, there were also found that there were some discrepancies found between EFL teachers beliefs and their practices in classroom teaching. They were in the component of learning objective, syllabus, and classroom management. There are some factors contribute to these discrepancies, namely (1) the teachers internal factors, (2) teachers external factor. The last, there are some factors contribute to shape the EFL teachers beliefs on the method of teaching English at MTs PPMI Assalaam Sukoharjo, namely (1) teachers experience as language learners; (2) experience from teaching; (3) expectation from the school, parents, the government, and the local society; and (4) training.